PENERAPAN KEPEMIMPINAN TRANSFORMASIONAL KEPALA SEKOLAH TERHADAP DISIPLIN KERJA GURU (STUDI KASUS SEKOLAH DASAR NEGERI 5 METESEH KECAMATAN BOJA) - Puji Rahayu; Noor Miyono (STKIP Subang, 2023)
Teacher work discipline is one of the factors that can support the success of a learning process in the school environment. However, the problem faced at SDN 5 Meteseh, Boja District, is that the presence of teachers arriving on time before working hours is still low, namely 55.25%. This shows that there are still several problems regarding the work discipline of teachers at SD Negeri 5 Meteseh in Boja District, Kendal Regency. Not only is attendance a problem, teachers' work discipline in making annual performance reports is still low and they often experience delays from the predetermined schedule, which has an impact on reducing teacher work discipline. Therefore, the problem of teacher work discipline needs to be considered more carefully, if it still occurs, then producing competent students will experience obstacles. From these problems, you must find the right solution to overcome them. Transformational leadership is an effort that can be made to improve teacher work discipline to become even better. The creation of good work discipline will create conducive conditions in schools. The implication of this research is the principal's transformational leadership to improve teacher work discipline so that the quality of student education in the 5 Meteseh State Primary School (SD) Boja District, if the leadership used by the school principal increases, it is certain that teacher work discipline will also increase so that it will have an impact. directly on the quality of education at the school.